ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE MERMELADA DE HORTALIZAS ZANAHORIA (DAUCUS CAROTA) Y ZAPALLO (CUCURBITA MAXIMA) EN LA CIUDAD DE LOJA - Salinas Armijos, Andrea Alexandra (2018)
The present research work aimed to carry out a feasibility project for the creation of a company producer and marketer of jam vegetable carrot (DAUCUS CAROTA) AND SQUASH (CUCURBITA MAXIMA) IN THE CITY OF LOJA, in order to obtain a utility to its owner and contribute to the socio-economic development of the city. To find out the feasibility of the project is conducted 397 surveys the different families of the city of Loja and interviewed and survey providers, and clients such as: Supermaxi, Galtor supermarket, great Aki Zerimar, Aunt S.A Ms. Dalia Granda, Ms. Graciela Ontaneda Mr. Jorge Valdivieso, Mr Manual Carpio Mr. Paul Chamba, selling jams in Loja being able to determine the predisposition of purchase of the product to prepare, tastes and preferences of the consumers, market conditions were analyzed by conducting a study. The materials that were estimated for the elaboration of this project are: human, material, technological and economic resources and in the includes methodology, the inductive method, which gave me to know the tastes and preferences of people with regard to the carrots with pumpkin jam; the deductive method, allowed conclusions to determine if is feasible or not the creation of the project. The discussion presents the details of studies, starting from the market study, whose purpose was to analyze the sector, the demand and supply for which a survey was conducted to 397 families and 10 suppliers of substitute products, knowing the demand unsatisfied 271.316 pounds, conditions of the competition and determining the marketing system through direct surveys applied to consumers of these products, thus getting the opportunity in the market, prices and advertising. The technical study aims to determine the size of the company, the plant distribution, and production process technology required, as also set the micro and macro location. In business organizational structure is proposed legal figure that will take the company and is made on the basis of the specific organizational requirements both structural and functional charts. Then is the description and analysis of each of the posts. En the financial study is considered to be all the necessary quantities to determine the initial investment that is $ 51.293,91 given to provide the elaboration of the State of profit and loss and projected cash flow, with established fixed and variable costs determined equilibrium depending on the installed capacity and the sales point. Finally the project assessment was carried out to establish their effectiveness and execution for which discussed the following indicators: the net present value (VAN) 41.177,17; the internal rate of return (IRR) 32.00 the relationship benefit cost (RB/C) 1.34; recovery period of capital (PRC) in 2 years, 8 months, 26 days, susceptibility testing with increase in costs is 12.16% and analysis decrease in income sensitivity is 9.27%, which showed that the implementation is favorable of the project. Once executed the necessary studies for the preparation of the project presented the necessary conclusions and recommendations of the research, the bibliography that served as reference theoretician for the culmination, the respective annexes and the index After the execution of the necessary studies for the preparation of the project it was concluded that the implementation of the producer and marketer company is viable marmalade carrots with pumpkin, according to the aforementioned financial indicators. Marmalade carrots with pumpkin, according to the aforementioned financial indicators product on the market, and thus ensure its profitability expected by the owner. Coming to the conclusion that it is important to promote this type of project creation of companies that meet the market needs, and promote investment in the town.